2021
DOI: 10.1111/ijmr.12256
|View full text |Cite
|
Sign up to set email alerts
|

A review of organizational research on acculturation from a nonwork–work spillover perspective: Content analysis and future research guidelines

Abstract: Acculturation has played an important role in understanding the behaviours, intergroup relations and adjustment of cultural minorities in their mainstream national culture. Additionally, organizational research has shown that acculturation is associated with a range of work‐related variables. Prior reviews on acculturation have not approached the literature from this angle, which we termed a nonwork–work spillover perspective on acculturation. To fill this gap, we conducted a content analysis of quantitative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 166 publications
0
2
0
Order By: Relevance
“…Adopting a more comprehensive approach to acculturation (Valenzuela et al, 2021), we concurrently explored immigrants’ actual and ideal acculturation, and HCNs’ perceived and preferred immigrant acculturation, in terms of behaviors, values, and identities in both work and private settings. Furthermore, we examined differences within and across settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting a more comprehensive approach to acculturation (Valenzuela et al, 2021), we concurrently explored immigrants’ actual and ideal acculturation, and HCNs’ perceived and preferred immigrant acculturation, in terms of behaviors, values, and identities in both work and private settings. Furthermore, we examined differences within and across settings.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive research on the topic, concerns regarding the lack of specificity in acculturation research have been raised. For example, Valenzuela et al (2021) identified several aspects of immigrant acculturation and HCN acculturation expectations based on prior work (Navas et al, 2005; Schwartz et al, 2010), including domain specificity, setting specificity, and actual–ideal specificity.…”
mentioning
confidence: 99%